Vagus nerve stimulation inhibits cortical spreading depression exclusively through central mechanisms. Issue 7 (July 2020) - Morais, Andreia; Liu, Tzu-Ting; Qin, Tao; Sadhegian, Homa; Ay, Ilknur; Yagmur, Damla; Mendes da Silva, Rosangela; Chung, David; Simon, Bruce; Guedes, Rubem; Chen, Shih-Pin; Wang, Shuu-Jiun; et al.
Abstract : Abstract: Experimental and clinical data strongly support vagus nerve stimulation (VNS) as a novel treatment in migraine. Vagus nerve stimulation acutely suppresses cortical spreading depression (CSD) susceptibility, an experimental model that has been used to screen for migraine therapies. However, mechanisms underlying VNS efficacy on CSD are unknown. Here, we interrogated the central and peripheral mechanisms using VNS delivered either invasively (iVNS) or noninvasively (nVNS) in male Sprague-Dawley rats. Cortical spreading depression susceptibility was evaluated 40 minutes after the stimulation. iVNS elevated the electrical CSD threshold more than 2-fold and decreased KCl-induced CSD frequency by 22% when delivered to intact vagus nerve. Distal vagotomy did not alter iVNS efficacy (2-fold higher threshold and 19% lower frequency in iVNS vs sham). By contrast, proximal vagotomy completely abolished iVNS effect on CSD. Pharmacological blockade of nucleus tractus solitarius, the main relay for vagal afferents, by lidocaine or glutamate receptor antagonist CNQX also prevented CSD suppression by nVNS. Supporting a role for both norepinephrine and serotonin, CSD suppression by nVNS was inhibited by more than 50% after abrogating norepinephrinergic or serotonergic neurotransmission alone using specific neurotoxins; abrogating both completely blocked the nVNS effect. Our results suggest that VNS inhibits CSD through central afferents relaying in nucleus tractus solitarius and projecting to subcortical neuromodulatory centers providing serotonergic and norepinephrinergic innervation to the cortex. Abstract : Supplemental Digital Content is Available in the Text.Selective vagotomy and neurotransmission depletion blocks vagus nerve stimulation efficacy on cortical spreading depression, indicating that activation of subcortical neuromodulatory projection centers mediates the effect throughout the brain.